Exercise-induced systemic and tumor-microenvironment adaptations regulating chemokine-guided immune-cell trafficking - Amir Hossein Ahmadi Hekmatikar; Aliakbar Yousefi-Ahmadipour; Diego Fernández-Lázaro (Clinical and Experimental Medicine, 2026)
Abstract Exercise is increasingly recognized as a biologically active intervention in cancer, yet its role in shaping the chemokine landscape of the tumor microenvironment remains incompletely defined. Importantly, immune-cell mobilization in the circulation does not necessarily translate into productive tumor infiltration, because effective homing depends on chemokine availability, endothelial permissiveness, stromal architecture, metabolic state, and spatial organization within the tumor microenvironment. In this review, we propose that exercise functions as a multiscale physiological regulator that may influence chemokine production, presentation, accessibility, and interpretation across transcriptional, vascular, stromal, and metabolic levels. We focus on three major axes relevant to immune-cell trafficking: CXCL9/10/11–CXCR3, CCL5–CCR5, and CXCL12–CXCR4. The CXCL9/10/11–CXCR3 pathway appears to provide the strongest mechanistic link between exercise-conditioned inflammatory signaling and cytotoxic T-cell recruitment. By contrast, CCL5–CCR5 is highly context dependent and may support either effector-cell trafficking or suppressive myeloid recruitment. CXCL12–CXCR4 likely represents a dominant retention and exclusion pathway associated with stromal sequestration, hypoxia, and vascular dysfunction. Although available evidence supports exercise-induced changes in systemic inflammatory mediators and selected circulating chemokines, direct evidence for reproducible exercise-driven remodeling of intratumoral chemokine gradients remains limited. Accordingly, exercise should not be viewed as a universal chemokine-normalizing intervention, but rather as a context-dependent modulator of immune accessibility that may be most effective when combined with immunotherapy, vascular normalization, or stromal-targeting strategies. Future work will require spatially resolved tumor analyses, rigorous exercise-dose reporting, serial sampling, and causal testing of exerkine–chemokine interactions.